PERANCANGAN MEDIA PROMOSI INDAH JAYA FURNITURE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Pramanda, In Mamal Siin Fara Dewinta; Kalijaga, Karsam; Bahruddin, Muh (Jurnal Art Nouveau, 2014)
Human needs of the objects or services is increasing, based on the increase of population and the rapid advancement of science and technology to human culture. Indah Jaya Furniture that helps support the primary needs of human beings, trying to build a brand identity that is able to give the image specifically for consumers so that it can be embedded in the mind of consumers. Has faced the crisis that impacts large enough for the company, although many efforts have been made to reach the target market is greater than ever. The purpose of this design is to designing media promotion Indah Jaya Furniture with efforts to increase brand awareness. Data analysis with indicators, STP, excess, weaknesses, opportunities and keywords that obtained using existing theories. From the analysis of data obtained the weakness of the Indah Jaya Furniture is a lack of consistency of the design concepts used in any media campaign, the low level of awareness on consumer. the design of the work refers to design principles and to formulate design concepts derived from the results of surveys, interviews, and other studies that the support. So, to increase brand awareness and give the results of the design according to the Indah Jaya Furniture image.